A medical implant molybdenum-rhenium alloy composite material and preparation method thereof
By adding silicon and calcium elements to the surface of molybdenum rhenium alloy and loading the composite functional coating of bioactive molecules and apatite, the problems of insufficient strength and poor biocompatibility of existing surgical implant materials are solved, and the bioactivity and antibacterial properties of molybdenum rhenium alloy composite materials are improved, and it is suitable for complex surgical implant applications.
Patent Information
- Application Number
- CN202510130762.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-06
AI Technical Summary
Existing surgical implant materials such as stainless steel, magnesium alloys and titanium alloys have problems such as insufficient strength, poor biocompatibility, and blurred image edges in clinical applications, which are difficult to meet the needs of complex surgical applications.
The ion implantation process is used to incorporate silicon and calcium elements on the surface of the molybdenum rhenium alloy, and the surface is loaded with a composite functional coating of bioactive molecules and apatite to form a stable composite material through chemical deposition.
It improves the bioactivity, antibacterial properties and biocompatibility of molybdenum-rhenium alloy composite materials, promotes the growth and integration of bone tissue, provides clearer medical images, and enhances the application prospects of the materials.
Smart Images

Figure CN119564922B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a medical implant molybdenum-rhenium alloy composite material and a preparation method thereof. Background Art
[0002] In the selection of surgical implant materials, common materials include stainless steel, magnesium alloys and titanium alloys. These materials each have certain advantages, but they also have defects that cannot be ignored in clinical applications. Taking stainless steel as an example, although it has low cost and good processing performance, its strength is relatively low, and it is often necessary to design and manufacture larger implants to meet the needs of specific parts, which not only increases the complexity of the operation, but may also cause greater pain and discomfort to patients. In addition, elements such as nickel (Ni) and chromium (Cr) rich in stainless steel are potentially harmful to the human body, which may cause allergic reactions and inflammatory reactions, affect biocompatibility, and lead to a higher rejection reaction.
[0003] As an emerging biomaterial, magnesium alloy has attracted attention due to its lightweight and good biocompatibility. However, the strength of magnesium alloy is still insufficient, and there is a problem of uneven corrosion in the in vivo environment, which may lead to premature failure of the implant. In addition, the density of magnesium alloy is low, and patients may experience blurred edges when undergoing medical imaging examinations, affecting the accuracy of diagnosis. Therefore, the application of magnesium alloy in surgical implant materials still needs to overcome many challenges.
[0004] Titanium alloy has become one of the mainstream choices for surgical implant materials due to its excellent biocompatibility and corrosion resistance. Titanium alloy has less rejection reaction when interacting with human tissue and can effectively reduce postoperative complications. However, the strength of titanium alloy is still insufficient, and its density is low, which may not meet the needs in some high-load applications. In addition, the performance of titanium alloy in medical images also has certain limitations, which may cause blurred image edges and affect doctors' judgment.
[0005] As a new type of surgical implant material, molybdenum-rhenium alloy has shown significant advantages. Molybdenum-rhenium alloy has excellent mechanical strength and high temperature resistance, and can work stably for a long time under high load and high temperature environment, meeting the needs of various complex surgical applications. Compared with other traditional materials, molybdenum-rhenium alloy also performs better in medical imaging, providing clear images and helping doctors make accurate diagnosis and treatment.
[0006] However, molybdenum-rhenium alloy materials as implant materials still face many problems, mainly including: poor or slow bone regeneration ability, poor integration with surrounding bone tissue, and average service life that cannot meet patients' needs. Since molybdenum-rhenium alloy is in contact with surrounding human tissues through its surface in the body, surface modification is of great practical significance for obtaining implants with excellent performance. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a medical implant molybdenum-rhenium alloy composite material and a preparation method thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] In a first aspect, the present invention provides a method for preparing a medical implant molybdenum-rhenium alloy composite material, comprising the following steps:
[0010] S1, using ion implantation process to dope silicon into the surface of molybdenum-rhenium alloy to obtain silicon-doped alloy material;
[0011] S2, using an ion implantation process to dope calcium into the surface of the silicon-doped alloy material to obtain a composite doped alloy material;
[0012] S3. placing the composite doped alloy material in a mixed solution of tea polyphenols, polyguanidine salt, calcium nitrate and phosphoric acid, heating the solution for reaction, and after the reaction is completed, washing and drying the solution to obtain a molybdenum-rhenium alloy composite material.
[0013] As a preferred embodiment of the technical solution of the present invention, in step S1, the parameters of the ion implantation process are: the vacuum degree is 2×10 -3 ~2.5×10 -3 Pa, the voltage is 43~45keV, the current is 1.8~2mA, and the dose of silicon is 3×10 18 ~5×10 18 Pieces / cm 2 .
[0014] As a preferred embodiment of the technical solution of the present invention, in step S2, the parameters of the ion implantation process are: the vacuum degree is 2×10 -3 ~2.5×10 -3 Pa, voltage is 43~45keV, current is 1.8~2mA, and calcium dose is 4×10 16 ~8×10 16 Pieces / cm 2 .
[0015] As a preferred embodiment of the technical solution of the present invention, in step S3, the concentration of tea polyphenols in the mixed solution is 2-4 g / L, and the concentration of polyguanidine salt is 1-2 g / L.
[0016] As a preferred embodiment of the technical solution of the present invention, in step S3, the polyguanidine salt is selected from at least one of polyhexamethyleneguanidine hydrochloride, polyhexamethyleneguanidine nitrate, and polyhexamethyleneguanidine carbonate.
[0017] As a preferred embodiment of the technical solution of the present invention, in step S3, the concentration of calcium nitrate in the mixed solution is 0.03-0.05 mol / L, and the concentration of phosphoric acid is 0.2-0.4 mol / L.
[0018] As a preferred embodiment of the technical solution of the present invention, in step S3, the heating reaction temperature is 40-60°C, and the heating reaction time is 12-18h.
[0019] As a preferred embodiment of the technical solution of the present invention, in step S3, the dosage ratio of the composite doped alloy material and the mixed solution is 1 g: 15-20 mL.
[0020] In a second aspect, the present invention provides a molybdenum-rhenium alloy composite material prepared by the above preparation method.
[0021] In a third aspect, the present invention also provides the use of the above-mentioned molybdenum-rhenium alloy composite material in the preparation of medical implant materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention uses molybdenum-rhenium alloy as the matrix material, first injects silicon element, then injects calcium element, and then loads a layer of composite functional coating of bioactive molecules and apatite on the surface. The prepared molybdenum-rhenium alloy composite material has excellent bioactivity and antibacterial properties.
[0024] (2) The present invention firstly incorporates silicon into the surface of the molybdenum-rhenium alloy, so as to form a certain silicide structure on the surface of the molybdenum-rhenium alloy, which is beneficial to the subsequent incorporation of calcium; then calcium is incorporated to form a calcium coating on its surface, thereby improving the biological activity of the molybdenum-rhenium alloy surface and providing active sites for the attachment of the composite functional coating; then, by means of chemical deposition, tea polyphenols and polyguanidine salts are attached to the surface of the composite doped alloy material through intermolecular cross-linking and chelation with calcium, and then combined with calcium ions and phosphate ions in the solution to form a composite functional coating of bioactive molecules and apatite on the surface of the material. The introduction of tea polyphenols and polyguanidine salts, on the one hand, improves the antibacterial properties of the molybdenum-rhenium alloy composite material, and on the other hand, improves the bonding force between apatite and the matrix material, thereby solving the technical problem that apatite is easy to fall off. By introducing apatite on the surface of the molybdenum-rhenium alloy, a good biological bond is formed between the molybdenum-rhenium alloy composite material and human bone tissue, thereby promoting the growth and integration of bone tissue and also improving the biological activity of the molybdenum-rhenium alloy composite material.
[0025] (3) The molybdenum-rhenium alloy composite material obtained in the present invention can be used in the preparation process of medical implant materials and has good practical value and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram showing the effects of different samples on the proliferation of rat BMSCs. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0028] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0029] The molybdenum-rhenium alloy used in the present invention is of the grade MoRe35%, which is purchased from Suzhou Xinghai Electronic Commerce Co., Ltd.
[0030] Example 1
[0031] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0032] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, the voltage is 45keV, the current is 2mA, and the dose of silicon is 4×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0033] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and calcium dose is 6×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0034] S3. Place 10g of the composite doped alloy material in 150mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 2g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 1g / L, the concentration of calcium nitrate is 0.04mol / L, and the concentration of phosphoric acid is 0.4mol / L. Heat the mixture at 40°C for 18h to react. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0035] Example 2
[0036] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0037] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and the dose of silicon is 3×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0038] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and calcium dose is 8×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0039] S3. Place 10 g of the composite doped alloy material in 200 mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 4 g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 1 g / L, the concentration of calcium nitrate is 0.03 mol / L, and the concentration of phosphoric acid is 0.2 mol / L. Heat the mixture at 60°C for 12 h. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0040] Example 3
[0041] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0042] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, the voltage is 45keV, the current is 2mA, and the dose of silicon is 5×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0043] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and calcium dose is 4×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0044] S3. Place 10 g of the composite doped alloy material in 150 mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 3 g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 2 g / L, the concentration of calcium nitrate is 0.03 mol / L, and the concentration of phosphoric acid is 0.3 mol / L. Heat the mixture at 50°C for 15 hours. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0045] Example 4
[0046] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0047] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2×10 -3 Pa, the voltage is 45 keV, the current is 1.8 mA, and the dose of silicon is 4.5×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0048] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2×10 -3 Pa, voltage is 45keV, current is 1.8mA, and calcium dose is 5×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0049] S3. Place 10 g of the composite doped alloy material in 200 mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 2 g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 2 g / L, the concentration of calcium nitrate is 0.05 mol / L, and the concentration of phosphoric acid is 0.2 mol / L. Heat the mixture at 50°C for 15 h. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0050] Comparative Example 1
[0051] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0052] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, the voltage is 45keV, the current is 2mA, and the dose of silicon is 4×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0053] S2. Place 10 g of silicon-doped alloy material in 150 mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 2 g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 1 g / L, the concentration of calcium nitrate is 0.04 mol / L, and the concentration of phosphoric acid is 0.4 mol / L. Heat the mixture at 40°C for 18 hours. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0054] Compared with Example 1, Comparative Example 1 does not perform calcium doping.
[0055] Comparative Example 2
[0056] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0057] S1. Calcium is doped into the surface of the molybdenum-rhenium alloy material by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and calcium dose is 6×10 16 Pieces / cm 2 , obtaining a calcium-doped alloy material;
[0058] S2. Place 10 g of calcium-doped alloy material in 150 mL of a mixed solution containing tea polyphenols, polyhexamethyleneguanidine hydrochloride, calcium nitrate and phosphoric acid, wherein the concentration of tea polyphenols in the mixed solution is 2 g / L, the concentration of polyhexamethyleneguanidine hydrochloride is 1 g / L, the concentration of calcium nitrate is 0.04 mol / L, and the concentration of phosphoric acid is 0.4 mol / L. Heat the mixture at 40°C for 18 hours. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0059] Compared with Example 1, Comparative Example 2 does not perform silicon doping.
[0060] Comparative Example 3
[0061] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0062] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, the voltage is 45keV, the current is 2mA, and the dose of silicon is 4×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0063] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2.5×10 -3Pa, voltage is 45keV, current is 2mA, and calcium dose is 6×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0064] S3. Place 10 g of the composite doped alloy material in 150 mL of a mixed solution containing calcium nitrate and phosphoric acid, wherein the concentration of calcium nitrate in the mixed solution is 0.04 mol / L and the concentration of phosphoric acid is 0.4 mol / L. Heat the mixture at 40°C for 18 hours. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0065] Compared with Example 1, in Comparative Example 3, tea polyphenols and polyhexamethyleneguanidine hydrochloride were not added.
[0066] Comparative Example 4
[0067] A method for preparing a medical implant molybdenum-rhenium alloy composite material comprises the following steps:
[0068] S1. The silicon element is doped into the surface of the molybdenum-rhenium alloy by ion implantation process. The parameters of the ion implantation process are: vacuum degree is 2.5×10 -3 Pa, the voltage is 45keV, the current is 2mA, and the dose of silicon is 4×10 18 Pieces / cm 2 , obtaining a silicon-doped alloy material;
[0069] S2, calcium is doped into the surface of silicon-doped alloy material by ion implantation process. The parameters of ion implantation process are: vacuum degree is 2.5×10 -3 Pa, voltage is 45keV, current is 2mA, and calcium dose is 6×10 16 Pieces / cm 2 , obtaining a composite doped alloy material;
[0070] S3. Place 10 g of the composite doped alloy material in 150 mL of a mixed solution containing tea polyphenols and polyhexamethyleneguanidine hydrochloride, wherein the concentration of tea polyphenols in the mixed solution is 2 g / L, and the concentration of polyhexamethyleneguanidine hydrochloride is 1 g / L. Heat the mixture at 40°C for 18 hours. After the reaction is completed, wash and dry the mixture to obtain a molybdenum-rhenium alloy composite material.
[0071] Compared with Example 1, Comparative Example 4 did not add calcium nitrate and phosphoric acid.
[0072] The molybdenum-rhenium alloy composite materials prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to performance testing, and the specific steps were as follows:
[0073] Antibacterial performance test: First, prepare 2×10 5cfu / ml bacterial suspension (Staphylococcus aureus ATCC6538, Escherichia coli ATCC8099), then place the sample materials to be tested flat in sterile plates, take 0.4mL of bacterial suspension and drop it in the center of the sample materials, spread it evenly, and cover it with a film; place it at 35℃ and relative humidity not less than 90% for 24 hours, then wash it, dilute it (PBS), count it after culture, and calculate the inhibition rate. Test it 3 times and take the average value of the results;
[0074] Biocompatibility performance test: carried out in accordance with ISO-10993-5-2009 in vitro cytotoxicity standard;
[0075] The test results are shown in Table 1:
[0076] Table 1
[0077] Staphylococcus aureus inhibition rate (%) Escherichia coli inhibition rate (%) Cytotoxicity Example 1 98.4 99.2 Level 0 Example 2 99.1 99.8 Level 0 Example 3 98.8 99.5 Level 0 Example 4 99.0 99.6 Level 0 Comparative Example 1 91.5 92.3 Level 0 Comparative Example 2 97.6 98.1 Level 0 Comparative Example 3 72.3 72.9 Level 0 Comparative Example 4 98.6 99.4 Level 0
[0078] As can be seen from Table 1, in Comparative Example 3, tea polyphenols and polyhexamethyleneguanidine hydrochloride were not added, and its antibacterial performance was significantly reduced. In Comparative Example 1, the molybdenum-rhenium alloy was not doped with calcium, and its antibacterial performance was reduced compared with Example 1. The reason may be that the binding force of tea polyphenols and polyguanidine salts with the silicon coating is not as good as that of the calcium coating, resulting in a reduction in the loading amount of tea polyphenols and polyguanidine salts, which in turn leads to a reduction in antibacterial performance.
[0079] The sample materials prepared in Example 1 and Comparative Examples 1-4 were used to test the proliferation performance of rat bone marrow mesenchymal stem cells (BMSCs), wherein rat bone marrow mesenchymal stem cells (BMSCs) and complete medium of rat bone marrow mesenchymal stem cells (BMSCs) were purchased from Saiye (Guangzhou) Biotechnology Co., Ltd. The specific steps of the test are as follows:
[0080] Rat BMSCs were 1×10 4 The density of cells / mL was planted on the surface of the sample material and incubated in complete culture medium for 3 and 7 days respectively. The proliferation of rat BMSCs was then detected using the CCK-8 method. The test results are as follows Figure 1 As shown in the figure, it can be seen that the molybdenum-rhenium alloy of Comparative Example 1 is not doped with calcium, and its cell proliferation level is lower than that of Example 1, indicating that the incorporation of calcium can improve the biological activity of the surface of the molybdenum-rhenium alloy; the molybdenum-rhenium alloy of Comparative Example 2 is not doped with silicon, and its cell proliferation level is lower than that of Example 1. The reason may be that no silicon element is doped, and the compatibility of the directly doped calcium element with the molybdenum-rhenium alloy is poor, which leads to a decrease in the cell proliferation level; in Comparative Example 3, tea polyphenols and polyhexamethyleneguanidine hydrochloride are not added, and in Comparative Example 4, calcium nitrate and phosphoric acid are not added, and their cell proliferation levels are lower than those of Example 1, indicating that the introduction of bioactive molecules and apatite can improve the biological activity of the molybdenum-rhenium alloy composite material.
[0081] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A method for preparing a medical implant molybdenum-rhenium alloy composite material, characterized in that: The steps include: S1, using ion implantation process to dope silicon into the surface of molybdenum-rhenium alloy to obtain silicon-doped alloy material; S2, using an ion implantation process to dope calcium into the surface of the silicon-doped alloy material to obtain a composite doped alloy material; S3. placing the composite doped alloy material in a mixed solution of tea polyphenols, polyguanidine salt, calcium nitrate and phosphoric acid, heating the solution for reaction, and after the reaction is completed, washing and drying the solution to obtain a molybdenum-rhenium alloy composite material.
2. The preparation method according to claim 1, characterized in that: In step S1, the parameters of the ion implantation process are: vacuum degree is 2×10 -3 ~2.5×10 -3 Pa, the voltage is 43~45keV, the current is 1.8~2mA, and the dose of silicon is 3×10 18 ~5×10 18 Pieces / cm 2 .
3. The preparation method according to claim 1, characterized in that: In step S2, the parameters of the ion implantation process are: vacuum degree is 2×10 -3 ~2.5×10 -3 Pa, voltage is 43~45keV, current is 1.8~2mA, and calcium dose is 4×10 16 ~8×10 16 Pieces / cm 2 .
4. The preparation method according to claim 1, characterized in that: In step S3, the concentration of tea polyphenols in the mixed solution is 2-4 g / L, and the concentration of polyguanidine salt is 1-2 g / L.
5. The preparation method according to claim 1, characterized in that: In step S3, the polyguanidine salt is selected from at least one of polyhexamethyleneguanidine hydrochloride, polyhexamethyleneguanidine nitrate, and polyhexamethyleneguanidine carbonate.
6. The preparation method according to claim 1, characterized in that: In step S3, the concentration of calcium nitrate in the mixed solution is 0.03-0.05 mol / L, and the concentration of phosphoric acid is 0.2-0.4 mol / L.
7. The preparation method according to claim 1, characterized in that: In step S3, the heating reaction temperature is 40-60° C., and the heating reaction time is 12-18 hours.
8. The preparation method according to claim 1, characterized in that: In step S3, the usage ratio of the composite doped alloy material and the mixed solution is 1 g:15-20 mL.
9. The molybdenum-rhenium alloy composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the molybdenum-rhenium alloy composite material according to claim 9 in preparing medical implant materials.
Citation Information
Patent Citations
Mo-Re-T series alloy as well as preparation method and application thereof
CN113913663A
Toughened and Corrosion- and Wear-Resistant Composite Structures and Fabrication Methods Thereof
US20090282949A1